Design and Implementation of a Mobile-Based Export-Import Digital Document Security System Using the AES-256 Encryption Algorithm to Ensure Data Confidentiality and Integrity - Bayu Adi Prasetyo; Rio Kurniawan; Suhendro Yusuf Irianto; Amnah (Jurnal Teknologi Informatika dan Komputer, 2026)
The increasing use of digital documents in export-import activities, especially in government agencies such as the Directorate General of Customs and Excise, has the potential to pose a threat of leaks if not supported by an adequate security system. The design of this security system aims to design and develop a web-based digital export-import document security system by implementing the Advanced Encryption Standard (AES) 256-bit encryption algorithm. The system development was carried out using the Waterfall method by utilizing PHP, HTML, CSS, JavaScript, and MySQL database technology. This system implements encryption and decryption mechanisms on export-import documents in PDF and DOCX formats. Test results indicate that encrypted documents cannot be accessed without a valid decryption process, and data integrity is maintained referring to the AES-256 validation results. This system is able to increase the level of digital document security and minimize the risk of data leaks in a web-based system environment. This research requires the addition of a multi-layer authentication mechanism, the implementation of a more comprehensive encryption key management system, and the development of applications for mobile platforms. The rapid development of information technology has changed the way individuals, organizations, and government institutions manage and distribute information. One of the main impacts is the increasing use of digital import-export documents as the primary medium for storing and exchanging critical data. These documents generally contain sensitive information, requiring security mechanisms capable of ensuring data confidentiality, integrity, and authenticity during storage and distribution.